Exploring students’ narratives: Understanding self-efficacy in vocabulary mastery - Ina Muftia; Listyaning Sumardiyani; Siti Nur'Aini (Universitas Muhammadiyah Malang, 2025)
This study aims to illustrate how students perceive their confidence level in their ability to learn the English language. One important factor in the learning process is self-efficacy, the belief that one can learn. This study aims to find out which vocabulary teaching strategies work best and to get students feedback on their preferred approach. This qualitative study uses pretest-post-test evaluation, questionnaire completion, and interviews with eighth-grade students at SMPN 24 Semarang. The results indicate that the majority of students have high self-efficacy and prefer the gamified online tool Duolingo for learning English vocabulary. Students also choose songs, dictionaries, peer group discussions, and mixed methods. The study's findings showed that the widespread use of Internet tools for vocabulary acquisition gives credence to their classroom use. This research is anticipated to shed further light on the connection between student language competence and self-efficacy.